2022
DOI: 10.1177/21925682211028587
|View full text |Cite
|
Sign up to set email alerts
|

Surface Navigation and the Influence of Navigation on MIS Surgery

Abstract: Study Design: Literature review. Objectives: To review the evidence for surface-based navigation in minimally-invasive spine surgery (MIS), provide an outline for its workflow, and present a wide range of MIS case examples in which surface-based navigation may be advantageous. Methods: A comprehensive review of the literature and compilation of findings related to surface-based navigation in MIS was performed. Workflow and case examples utilizing surface-based navigation were described. Results: The nascent li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In recent years, some initial studies about accurate medicine attract people's attention, many technology were used to improve the accuracy of pedicle screw insertion, such as computer-based navigation and robotic-assisted guidance systems [20][21][22][23][24] , pedicle screw entry point [25][26][27] , TPA of lumbar 17,18,28 , both scan-and-plan registration and CT-to-uoroscopy registration methods is similar uoroscopy time exposure 29 . Still, recent reviews demonstrate that these instrument are no better than freehand technologies, but also substantially increase the costs and operation time 12,30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some initial studies about accurate medicine attract people's attention, many technology were used to improve the accuracy of pedicle screw insertion, such as computer-based navigation and robotic-assisted guidance systems [20][21][22][23][24] , pedicle screw entry point [25][26][27] , TPA of lumbar 17,18,28 , both scan-and-plan registration and CT-to-uoroscopy registration methods is similar uoroscopy time exposure 29 . Still, recent reviews demonstrate that these instrument are no better than freehand technologies, but also substantially increase the costs and operation time 12,30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…The radiation exposure is clearly larger in microendoscopic discectomy. However, fluoroscopy delivers a two-dimensional image in one plane of orientation, and placement of guidewires during microendoscopic discectomy can be challenging because several punctures might be needed to position the guidewires adequately [1]. Three-dimensional navigation and robotic assistance can considerably improve accuracy during positioning [5, 9].…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
“…L. F. H. Theyse ✉, College of Veterinary Medicine, Department for Small Animals, University of Leipzig, An den Tierkliniken 23, D-04103 Leipzig, Germany, Email: lars. theyse@kleintierklinik.uni-leipzig.de guidewires adequately [1]. Threedimensional navigation and robotic assistance can considerably improve accuracy during positioning [5,9].…”
mentioning
confidence: 99%
“…1 Spine surgery has followed suit with the evolution of navigation and robotics over the last two decades as new imaging and assistive modalities. [2][3][4][5][6][7][8][9] In comparing the two modalities for lumbar spine surgery, several studies have demonstrated the potential benefits of robotics over navigation. Roboticassisted pedicle screws have been shown to have greater accuracy 10,11 and allow for greater screw diameter and length when compared with navigation, resulting in more optimal screw placement.…”
mentioning
confidence: 99%
“…Across all fields of surgical practice, there has been a significant shift toward the adaptation of new technologies in the operating room 1 . Spine surgery has followed suit with the evolution of navigation and robotics over the last two decades as new imaging and assistive modalities 2–9 . In comparing the two modalities for lumbar spine surgery, several studies have demonstrated the potential benefits of robotics over navigation.…”
mentioning
confidence: 99%